Chemical sensors and biosensors - Eggins, Brian R. (Analytical techniques in the sciences., 2002)
Covering the huge developments in sensor technology and electronic sensing devices that have occurred in the last 10 years, this book uses an open learning format to encourage reader understanding of the subject.: An invaluable distance learning book; Applications orientated providing invaluable aid for anyone wishing to use chemical and biosensors. Key features and subjects covered include the following: Sensors based on both electrochemical and photometric transducers; Mass-sensitive sensors; Thermal-sensitive sensors; Performance factors for sensors; Examples of applications; Detailed case.